Process Improvement Hypothesis Testing in an e-Procurement Implementation Assessment Model Framework: A Case Study of Bangladesh's Roads and Highways Division (British Journal of Multidisciplinary and Advanced Studies, 2023)
Using the policy tools PPA-2006 and PPR-2008, the use of manual tendering by public procurement agencies has traditionally been continues in Bangladesh. But it had some challenges in terms of process improvement. The e-Government Procurement (e-GP) guideline 2011 is adopted to address this issue and lunched e-GP system in public procurement.  However, since the e-GP system was first implemented, a great deal of investigations or analyses have not been conducted to determine how well its tender process improvement is being assessed. This study aims to investigate the essential variables that contribute to the successful implementation of an electronic procurement system in Bangladesh. Another goal is to build an efficient e-procurement implementation assessment model. Survey questionnaires were employed to collect data from eleven zones in Roads and Highways Division (RHD) as a population. The study sample size was 206 Procurement Entities (PE) engineers. Hypothesis test has been done choosing MLR model using SPSS software. Process improvement was one of the eight hypothesis tests in the study. The results demonstrated that the model was fit. Academicians, students, e-GP users, procurement professionals, and researchers will benefit from the study's findings. The study's original contribution is the creation of a theoretical design for the RHD e-procurement implementation assessment model.